2019
DOI: 10.1080/16549716.2019.1670002
|View full text |Cite
|
Sign up to set email alerts
|

Gender responsive multidisciplinary doctoral training program: the Consortium for Advanced Research Training in Africa (CARTA) experience

Abstract: Doctoral training has increasingly become the requirement for faculty in institutions of higher learning in Africa. Africa, however, still lacks sufficient capacity to conduct research, with just 1.4% of all published research authored by African researchers. Similarly, women in Sub-Saharan Africa only constitute 30% of the continent’s researchers, and correspondingly publish little research. Challenging these gendered inequities requires a gender responsive doctoral program that caters for women’s gender role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…The number of male fellows publishing cross-CARTA Total number of fellows 185 20 18 22 27 22 24 26 26 African partner institutions University of Ibadan 28 2 3 4 3 4 4 4 4 University of Malawi 26 4 4 3 2 3 3 4 2 Obafemi Awolowo University 24 3 1 3 3 2 4 4 4 University of Witwatersrand 23 3 2 2 4 2 4 3 3 Makerere University 19 -4 1 4 3 2 2 3 University of Nairobi 18 1 1 2 2 2 3 fellows' publications was greater than that of female fellows. While gender equity in CARTA has been achieved across the entire programme [16], the early cohorts comprised more men than women. This may explain to some extent, the lower output by women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of male fellows publishing cross-CARTA Total number of fellows 185 20 18 22 27 22 24 26 26 African partner institutions University of Ibadan 28 2 3 4 3 4 4 4 4 University of Malawi 26 4 4 3 2 3 3 4 2 Obafemi Awolowo University 24 3 1 3 3 2 4 4 4 University of Witwatersrand 23 3 2 2 4 2 4 3 3 Makerere University 19 -4 1 4 3 2 2 3 University of Nairobi 18 1 1 2 2 2 3 fellows' publications was greater than that of female fellows. While gender equity in CARTA has been achieved across the entire programme [16], the early cohorts comprised more men than women. This may explain to some extent, the lower output by women.…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that additional responsibilities traditionally assigned to women such as childcare and other household chores may mean women have less time to work on publications [21,22]. CARTA's efforts to build cross-cohort, crossinstitutional and multidisciplinary collaborations were realised by recruiting fellows from multiple disciplines and different institutions, and organizing crossinstitutional and cross-cohort seminars and encouraging cross-institutional registration [16]. We found that this did result in publications between fellows and in particular across institutions and disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…This study also presents new insights on the challenges related to marital and parental status by indicating that these are not just practical challenges around provision of childcare but also symbolic ones around normative 'availability' and expectations of women to prioritise families rather than careers. In a recent study, Khisa and colleagues [32] have highlighted the positive outcome of supporting women's practical gender needs around childbearing and caring through nancially supporting husbands to travel with their spouse to provide childcare during short and long-term travel. The authors contend that such efforts are beginning to pay off through men/fathers playing a more active role in childcare even on return.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently such an initiative may support shifting the patriarchal gendered institution of family to be more accommodating to women to successfully pursue careers in science research [32]. However, how this might play out for dual and non-dual scienti c career couples remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation